Supporting efforts to address malnutrition in the context of the COVID-19 pandemic in India: An emergency need - Menon, Purnima; de Wagt, Arjan; Reddy, Vignesh; Reddy, Kartheek; Pandav, Chandrakant Sambhaji; Avula, Rasmi; Mathews, Pratima (Wolters Kluwer, 2021)
India has been on a steady march to address malnutrition in the last decade. The nutrition community has worked on building consensus on key actions, implementation platforms were put in place and financing for nutrition slowly increased. Under the strong leadership of the Prime Minister, a revolutionary program to address malnutrition was launched in 2018. As actions under the mission accelerated, the COVID-19 pandemic arrived in early 2020. Affecting health systems, food systems, nutrition programs, social safety nets, and the economy, the pandemic has the potential to exacerbate the challenge of malnutrition in multiple ways. India can mitigate some of the possible ways in which COVID-19 will affect malnutrition but will require strong leadership and continued commitment, adaptation of the national nutrition mission, strengthening of the social safety net and innovative evidence-based data to take informed decisions, implement them and ensure feedback to take necessary corrective action. In this article, we outline some challenges and key areas for action. We conclude that India's nutrition journey is too important to be derailed by a crisis like COVID-19. This is a clarion call for the nutrition community in India to rally strongly to support continued attention to malnutrition in all its forms, to generate relevant evidence, and to support and engage all of society to urgently and adequately address malnutrition in the context of the COVID-19 pandemic. We have come too far to turn back now.